808 Exploring resistance mechanism to pembrolizumab and ang-2 inhibitor trebananib (NCT03239145) using high-dimensional single-cell mass cytometry (CyTOF). (10th December 2020) - Rahma, Osama; Baginska, Joanna; Brainard, Martha; Giobbie-Hurder, Anita; Tyan, Kevin; Cleary, James; Schlechter, Benjamin; Maloney, Anna; Manos, Michael; Romee, Rizwan; Severgnini, Mariano; Stephen Hodi, F
Abstract : Background: Angiogenesis is mediated by both the vascular endothelial growth factor (VEGF) family and the angiopoietin (Ang1-2)/Tie-2 pathway. 1-3 We demonstrated that increased soluble VEGF and ang-2 is associated with decreased benefit to immune checkpoint inhibitors (ICIs). 4 We then initiated a clinical trial combining pembrolizumab and ang-1/2 inhibitor (trebananib) (NCT03239145 ) with expansion cohorts in microsatellite stable (MSS) colorectal cancer (CRC), ovarian and renal cell cancer. 5 We present the correlative analysis using high-dimensional single-cell mass cytometry (CyTOF) to characterize the effects of the combination therapy and examine differences between patients according to clinical benefit. Methods: We used two separate CyTOF panels to monitor 48 markers of innate and adaptive immune populations in 26 evaluable patients who received the PR2D of trebananib (30mg/kg). Mass cytometry assay was performed on peripheral blood mononuclear cells of 26 patients at baseline (C1D1), 16 patients at cycle 3 day 1 (C3D1), and 4 patients at cycle 9 day 1 (C9D1). We compared immune cell markers between patients with clinical benefit (CB) and patients with no clinical benefit (NCB). Results: Of 26 patients (16 CRC, 8 ovarian, 2 RCC), 11 patients had confirmed PR (3) or SD (8) resulting in CB of 42.3% while 15 patients had NCB. Independent of CB, there were statistically significant decreases from C1D1 to C3D1 in naïve CD8+ T cells (p=0.03), CD4+ T central memory cells (p=0.05), and PD-1+/CD4+ and CD8+ T cells (p<0.0001). In NCB patients, there was a statistically significant decrease from C1D1 to C3D1 in CD3+ T cells (p=0.009), CD4+/CXCR3+ T cells (p=0.02), CD8+/CXCR3+ T cells (p=0.02), and CD8+ T effector memory cells (p=0.03) while no significant changes in these T cell populations were observed in CB patients ( figure 1 ). In NCB patients, monocytic myeloid-derived suppressor cells (p=0.003) and classical monocytes increased from C1D1 to C3D1 (p=0.01) while there was no significant change in this population in CB patients ( figure 2 ). Interestingly, CB patients had higher activated CD56+NKp30+ at baseline (p= 0.03) with increased cytolytic CD56 dim CD16+ population from C1D1 to C3D1 (p= 0.04) compared to NCB patients ( figure 3 ). Conclusions: Our findings suggest that the activity of anti-PD-1 and ang-2 peptibody (trebananib) combination is hindered by an increase in immunosuppressive myeloid cells leading to decrease in memory and effector T cell populations. The association between baseline activated NK cell and the expansion of cytolytic NK cells with favorable outcomes should be further explored. Trial Registration: NCT03239145 Ethics Approval: The study was approved by the Institutional Review Board (IRB) at Dana-Farber Cancer Institute for NCT03239145 . Consent: Written informed consent was obtained from the patient for participation in this study and publication of data. References: Gerald D, Chintharlapalli S, Augustin HG, Benjamin LE. Angiopoietin-2: an attractive target for improved antiangiogenic tumor therapy. Cancer Research 2013;73 :1649-57. Augustin HG, Koh GY, Thurston G, Alitalo K. Control of vascular morphogenesis and homeostasis through the angiopoietin-Tie system. Nature Reviews Molecular Cell Biology 2009;10 :165-77. Rahma OE, Hodi FS. The Intersection between Tumor Angiogenesis and Immune Suppression. Clin Cancer Res 2019;15; 25(18):5449-5457. Yuan J, Zhou J, Hodi FS, et al. Pretreatment serum VEGF is associated with clinical response and overall survival in advanced melanoma patients treated with ipilimumab. Cancer Immunol Res 2014 Feb;2(2):127-32. Rahma OE, Cleary J, Hodi FS, et al. Phase Ib study of pembrolizumab and trebananib (angiopoietin-2 inhibitor [Ang-2]): Preliminary analysis of the colorectal cancer (CRC) cohort. GI ASCO, San Francisco, 2019.